Out-of-plane principal stress in plane strain/stress failure investigations – an overview of its relevance for various failure criteria - BEDNÁRIK, Martin; KOHÚT, Igor (Contributions to Geophysics and Geodesy, 2021)
The paper exposes the role of the out-of-plane principal stress in the investigations of (brittle) failure of isotropic linear elastic continuum using plane strain (or plane stress) approximations. The plots in (σm, τm), (σ3, σ1) spaces for each of the examined criteria: the two-dimensional: Coulomb, Tresca, Hoek-Brown, and the three-dimensional ones: Drucker-Prager and linear Mogi, give an insight into the interplay of Poisson ratio and the material parameters involved in the respective criterion formula.